Disaffection and Realpolitik in Elizabeth Bowen's The Heat of the Day. Issue 9 (21st October 2019) - Underland, Nathaniel
ABSTRACT: Elizabeth Bowen's quintessential Blitz-era novel, The Heat of the Day (1948), is also an artefact of the nascent Cold War. The novel casts Cold War international relations as a problem of literary realism's presentation of a 'whole' picture, and it stages disaffection with literary realism in order to object also to Soviet-style realpolitik . For Bowen, both political and literary realism are Machiavellian in their emphasis on effect. Both assume that the end justifies the means because both argue that comprehension of a 'whole' picture, whether of a struggle for power in realpolitik or of a reality effect in literary realism, renders moot the specific method for arriving at this result. The Heat of the Day 's disaffection with literary realism testifies to Bowen's postwar desire for a returned focus on means – that is, to a 'principled' liberal internationalism rather than realpolitik . By looking at the composition history of The Heat of the Day and at Bowen's postwar reviews of existentialist fiction, particularly by Jean-Paul Sartre, this essay shows how Bowen's method originates in a surprising source: existentialism. The Heat of the Day testifies to how, in the immediate postwar era, internationalist response was seen as a product of individual responsibility.